2018
DOI: 10.1101/242347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comprehensive Tool Set for Inducible, Cell Type-Specific Gene Expression in Arabidopsis

Abstract: Understanding the context-specific role of gene function is a key objective of modern biology. To this end, we generated a resource for inducible cell-type specific trans-activation based on the well-established combination of the chimeric GR-LhG4 transcription factor and the synthetic pOp promoter. Harnessing the flexibility of the GreenGate cloning system, we produced a comprehensive set of GR-LhG4 driver lines targeting most tissues in the Arabidopsis shoot and root with a strong focus on the indeterminate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Recently, a comprehensive tool set of inducible activator/driver lines targeting most cell types in Arabidopsis , with the focus on the three main meristems (RAM, SAM and the cambium), was created by Schurholz et al. ().…”
Section: Strategic Planningmentioning
confidence: 99%
“…Recently, a comprehensive tool set of inducible activator/driver lines targeting most cell types in Arabidopsis , with the focus on the three main meristems (RAM, SAM and the cambium), was created by Schurholz et al. ().…”
Section: Strategic Planningmentioning
confidence: 99%
“…Promoter analysis of EXPA10, EXPA14 and EXPA15 identifies ChIP-seq derived binding events for transcription factors (type-B ARABIDOPSIS RESPONSE REGULATORS, ARRs) involved in the cytokinin signalling pathway. Red, blue and green colours depict the peaks from Xie et al, 2018, Zubo et al, 2017and O'Malley et al, 2016 (A) Double hemizygous F1 progeny of a cross between pEXPA14::EXPA14:mCherry and endodermis-specific pSCR>GR>mTurquoise2 (Schurholz et al, 2018). In the transversal (xz) optical section of a primary root, the EXPA14 (red) localizes to cortex, endodermis and background autofluorescence in epidermis is in green.…”
Section: Discussionmentioning
confidence: 99%
“…In the transversal (xz) optical section of a primary root, the EXPA14 (red) localizes to cortex, endodermis and background autofluorescence in epidermis is in green. (B) Double hemizygous F1 progeny of a cross between pEXPA15::EXPA15:mCherry and phloem-specific pSMXL5>GR>mTurquoise2 (Schurholz et al, 2018)In the z-stack projection of an emerging lateral root EXPA15 (red) localizes to the CW of epidermis, phloem is in green. The 7-day old Arabidopsis seedlings were grown on MS media +Dex to induce the mTurquoise2 ER-specific expression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the homolog of the Arabidopsis thaliana LIPID TRANSFER PROTEIN 1 (AT2G38540, LTP1) that is expressed in epidermal cells (Thoma et al, 1994;Abe et al, 2001;Baroux et al, 2001) is expressed in LCM-derived sorghum stem epidermal cells (Supplemental Data Set 2). Similarly, ALTERED PHLOEM DEVELOPMENT (AT1G79430, APL) that is expressed in Arabidopsis inflorescence stem phloem cells (Abe et al, 2015;Schürholz et al, 2018) and MYB DOMAIN PROTEIN 103 (AT1G63910, AtMYB103) and SULFATE TRANSPORTER 1;2 (AT1G78000, SULTR1;2), genes that are expressed in xylem cells (Zhong et al, 2008), are differentially expressed in the corresponding LCM-derived sorghum stem cell types (Supplemental Data Set 2). No definitive marker gene has been reported for stem pith parenchyma cells (Shi et al, 2021); however, 66 genes with the pith-preferred expression pattern identified in a LCM study of the inflorescence stem in Arabidopsis (Shi et al, 2021) are expressed in a highly specific manner in sorghum stem pith parenchyma cells (Supplemental Data Set 2).…”
Section: Sorghum Stem Cell Types Have Distinct Transcriptomesmentioning
confidence: 99%